Survival rate variation among different types of hospitalized traumatic cardiac arrest: A retrospective and nationwide study. Issue 28 (July 2018) - Lai, Chung-Yu; Tsai, Shih-Hung; Lin, Fu-Huang; Chu, Hsin; Ku, Chih-Hung; Wu, Chun-Hsien; Chung, Chi-Hsiang; Chien, Wu-Chien; Tsai, Ching-Tsan; Hsu, Huan-Ming; Chu, Chi-Ming
Abstract : Abstract: Studies regarding the prognostic factors for survival conditions and the proportions of survival to discharge among different types of hospitalized traumatic cardiac arrest (TCA) during the period of postresuscitation are limited. This nationwide study was designed to determine certain parameters and clarify the effect of various injuries on the survival of hospitalized TCA patients to discharge. Data were retrieved from the National Health Insurance Research Database (NHIRD) from 2007 to 2013 in Taiwan. We reviewed patients with a diagnosis of TCA using International Classification of Disease Clinical Modification, 9th revision codes (ICD-9-CM codes). Patients identified for analysis were simultaneously coded in traumatic etiology (ICD-9-CM codes: 800–999) and cardiac arrest (ICD-9-CM codes: 427.41 or 427.5). The determinants and effects of different types of injury on survival were evaluated by SPSS 22.0 (IBM, Armonk, NY). A total of 3481 cases of hospitalized TCA were selected from the NHIRD. The overall rate of survival to discharge was 22.1%. The results indicated a decreased adjusted odds ratio (aOR) of survival to discharge with higher numbers of organ failure (aOR: 0.82; 95% confidence interval [CI]: 0.73–0.92). Patients with ventricular fibrillation had a better discharge rate (aOR: 4.33; 95% CI: 3.29–5.70). Two parameters, transfer to another hospital and the number of intensive care unit beds, were positively correlated with survival. Compared with traffic accidents, different injuries associated with survival to discharge were identified; the aOR (95% CI) was 1.89 (1.12–3.19) for poisoning, 1.63 (1.13–2.36) for falls, and 2.00 (1.36–2.92) for drowning/suffocation. This study has shown that hospitalized TCA patients with multiple organ failure may be less likely to be discharged from the hospital. The presence of ventricular fibrillation rhythm on admission increased the odds of survival to discharge. In the phase of postcardiac arrest care, the number of intensive care unit beds and transfer to another hospital were positively correlated with survival. Those events attributed to traffic accidents have a much worse influence on the main outcome. Abstract : Supplemental Digital Content is available in the text